2008
DOI: 10.1073/pnas.0809395105
|View full text |Cite
|
Sign up to set email alerts
|

Plant CLE peptides from two distinct functional classes synergistically induce division of vascular cells

Abstract: The Clavata3 (CLV3)/endosperm surrounding region (CLE) signaling peptides are encoded in large plant gene families. CLV3 and the other A-type CLE peptides promote cell differentiation in root and shoot apical meristems, whereas the B-type peptides (CLE41-CLE44) do not. Instead, CLE41 inhibits the differentiation of Zinnia elegans tracheary elements. To test whether CLE genes might code for antagonistic or synergistic functions, peptides from both types were combined through overexpression within or application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
216
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(244 citation statements)
references
References 47 publications
12
216
2
2
Order By: Relevance
“…MtCLE12 and MtCLE13 are most similar to a group of less characterized Arabidopsis CLE peptides (AtCLE1-AtCLE7) that are broadly produced with higher activity levels in the root (Sharma et al, 2003;Ito et al, 2006). Exogenous peptide addition did not suppress procambial-to-xylem cell transdifferentiation in a zinnia cell culture, while application of high, but not low, concentrations of peptides resulted in primary root meristem arrest (Ito et al, 2006;Strabala et al, 2006;Kinoshita et al, 2007;Whitford et al, 2008). Furthermore, ectopic overexpression of this group of peptides resulted in root elongation, mild wus loss-of-function phenotypes, mild distorted leaves, and dwarfing in later growth stages (Strabala et al, 2006).…”
Section: Discussion Cle Family In M Truncatulamentioning
confidence: 99%
See 2 more Smart Citations
“…MtCLE12 and MtCLE13 are most similar to a group of less characterized Arabidopsis CLE peptides (AtCLE1-AtCLE7) that are broadly produced with higher activity levels in the root (Sharma et al, 2003;Ito et al, 2006). Exogenous peptide addition did not suppress procambial-to-xylem cell transdifferentiation in a zinnia cell culture, while application of high, but not low, concentrations of peptides resulted in primary root meristem arrest (Ito et al, 2006;Strabala et al, 2006;Kinoshita et al, 2007;Whitford et al, 2008). Furthermore, ectopic overexpression of this group of peptides resulted in root elongation, mild wus loss-of-function phenotypes, mild distorted leaves, and dwarfing in later growth stages (Strabala et al, 2006).…”
Section: Discussion Cle Family In M Truncatulamentioning
confidence: 99%
“…Studies on the putative CLE peptides of Arabidopsis (Ito et al, 2006;Ni and Clark, 2006;Strabala et al, 2006;Whitford et al, 2008) have shown a direct relationship between CLE domain sequence and induced phenotypes. MtCLE12 and MtCLE13 are most similar to a group of less characterized Arabidopsis CLE peptides (AtCLE1-AtCLE7) that are broadly produced with higher activity levels in the root (Sharma et al, 2003;Ito et al, 2006).…”
Section: Discussion Cle Family In M Truncatulamentioning
confidence: 99%
See 1 more Smart Citation
“…TRACHEARY ELEMENT DIFFERENTIATION INHIBITORY FACTOR (TDIF)/ CLE41/CLE44 peptide regulates vascular development in Arabidopsis. TDIF peptide derived from CLE41 or CLE44 is perceived by PHLOEM INTERCALATED WITH XYLEM (PXY), an LRR-RLK [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This approach indeed established TDR/PXY as a CLE41/44 receptor in the regulation of vascular stem cells (Hirakawa et al 2008). The overexpression of CLE41 resulted in pleiotropic phenotypes, including a dwarf appearance with numerous bushy, small leaves, suggesting that CLE41/44 is involved in many biological processes other than vascular meristem maintenance (Whitford et al 2008).…”
Section: Lrr-containing Receptors Mediate Cle Peptide Signalingmentioning
confidence: 99%